Linking teacher support to achievement emotion profile: the mediating role of basic psychological need satisfaction - Yang, Yang; Gong, Shaoying; Cao, Yang; Qiu, Yin; Xu, Xizheng; Wang, Yanqing (Frontiers in Psychology, 2024)
The current study used a person-centered approach to explore the co-occurrence of college students’ achievement emotions. It also examined the impact of teacher support on achievement emotion profiles and the mediating effect of need satisfaction. A total of 866 college students participated in the survey. A robust three-step latent profile analysis was employed to analyze the data. Four profiles of achievement emotions were identified: moderate mixed emotions, the blends of high positive emotions, the blends of moderate positive emotions, and high mixed emotions. Higher perceived teacher support was associated with a greater likelihood of being classified into the blends of moderate positive emotion profile or the blends of high positive emotion profile. Moreover, basic psychological need satisfaction mediated the relationship between teacher support and the four emotion profiles. Our findings contribute to a more comprehensive understanding of the role of teacher support in shaping achievement emotion profiles, helping to broaden the application of self-determination theory to explain the mechanism by which external support influences emotion profiles.